If-Clauses, their grammatical consequents, and their embodied consequence: organizing joint attention in guided tours - De Stefani, Elwys (Frontiers in communication, 2021)
In linguistics, if-clauses have attracted the interest of scholars working on syntax, typology and pragmatics alike. This article examines if-clauses as a resource available to tour guides for reorienting the visitors’ visual attention towards an object of interest. The data stem from 11 video-recorded tours in Italian, French, German and Dutch (interpreted into Flemish Sign Language). In this setting, guides recurrently use if-clauses to organize a joint focus of attention, by soliciting the visitors to bodily and visually rearrange. These clauses occur in combination with verbs of vision (e.g., to look), or relating to movement in space (e.g., to turn around). Using conversation analysis and interactional linguistics, this study pursues three interrelated objectives: 1) it examines the grammatical relationship that speakers establish between the if-clause and the projected main clause; 2) it analyzes the embodied conduct of participants in the accomplishment of if/then-constructions; 3) it describes if-clauses as grammatical resources with a twofold projection potential: a vocal-grammatical projection enabling the guide (or the addressees) to achieve a grammatically adequate turn-continuation, and an embodied-action projection, which solicits visitors to accomplish a situationally relevant action, such as reorienting gaze towards an object of interest. These projections do not run independently from each other. The analysis shows how, while producing an if-clause, guides adjust their emerging talk—through pauses, expansions and restarts—to the visitors’ co-occurring spatial repositioning. These practices are described as micro-sequential adjustments that reflexively affect turn-construction and embodied compliance. In addressing the above phenomena and questions, this article highlights the fundamentally adaptive, situated and action-sensitive nature of grammar.